Efficiency-enhancing effects of private and collective enterprises in transitional China - Ivo Bischoff (Justus-Liebig-Universität Gießen, Zentrum für Internationale Entwicklungs- und Umweltforschung (ZEU), 2002)
Private and collective enterprises are expected to increase overall efficiency in transitional China, partly because they are more efficient than state owned enterprises. More importantly, this paper argues, they induce efficiency gains in state owned enterprises and the economy as a whole. Empirical evidence from 28 Chinese provinces between 1993 and 1998 gives support to this hypothesis by showing that the activity levels of private enterprises and rural collective enterprises have a positive effect on regional labor productivity.
Keywords: D24; P21; 330; China; private enterprises; collective enterprises; efficiency; labor productivity; Privatwirtschaft; Sozialistisches Unternehmen; Übergangswirtschaft; Arbeitsproduktivität; Wirtschaftliche Effizienz; Schätzung; China